Applied Mixed Methods in Oral Health Research: Importance and Example of a Training Program. (July 2017) - Nicolau, B.; Castonguay, G.; Levine, A.; Hong, Q.N.; ,; Pluye, P.
Knowledge Transfer Statement: Mixed methods are increasingly being used in research studies on complex oral health issues. Combining quantitative and qualitative approaches, this methodology produces in-depth results of great relevance to researchers, clinicians, managers, and policy makers at each level of the oral health care system. A 5-day training program in applying oral health mixed methods research can be replicated by other institutions and contribute to capacity building and training faculty, students, and research professionals.